Conventional insulin pump therapy in two neonatal diabetes patients harboring the homozygous PTF1A enhancer mutation: Need for a novel approach for the management of neonatal diabetes - Erdal Kurnaz; Zehra Aycan; Nurdan Yıldırım; Semra Çetinkaya (The Turkish Journal of Pediatrics)
The enhancer of PTF1A mutation causes developmental defects of the pancreas. This condition can result in insulin-requiring diabetes and exocrine pancreatic insufficiency. We report two patients with diabetes mellitus harboring the homozygous PTF1A enhancer mutation. The patients had hyperglycemia in the first month of life and were started with subcutaneous insulin injections with NPH insulin. When blood glucose (BG) exceeded 250 mg/dl, a conservative dose of rapid-acting insulin was administered to restore BG to the target range. In cases with documented poor control (persistent hypoglycemia and rebound hyperglycemia), it was decided that the baby would benefit from a continuous subcutaneous insulin infusion pump. But our experience shows that wide fluctuations in BG concentrations despite the strict follow-up was probably due to the absence of circulating glucagon. Further treatment options would overcome this problem, especially for children with pancreas agenesis. We could say theoretically that using diluted insulin, a sensor-augmented insulin pump system and single-hormone (insulin alone) and dual-hormone (insulin and glucagon) artificial pancreas systems may mitigate the severity of hypogylcemia.